(untitled) (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2023)
The Tangkolak mangrove ecotourism area is one of natural attractions, namely a mangrove forest in Sukakerta Village, East Cilamaya Sub-district, Karawang Regency, West Java Province. The mangrove ecotourism of Tangkolak currently have no management and low visitor. This research aims to describe the potential and identify applicable strategies through internal-external factor analysis within the Tangkolak mangrove ecotourism area. Four station points revealed a potential of 14 mangrove vegetation species and 10 fauna species. The most mangrove species all stations is Rhizophora apiculata, while the dominant fauna is Ciconia sp. The mangrove vegetation in the Tangkolak mangrove ecotourism area exhibits a low diversity index (H’) and there’s no dominating species in each stations, whereas the fauna in the area showcases varied diversity index values with Ciconia sp. as the dominant species. Visitors and local fishermen in the surrounding community utilize fishing tools like a fishing rods, traps, and nets when catching fish in the vicinity of the mangrove ecotourism area. The development strategy is determined using SWOT analysis. The results of IFAS and EFAS analyses indicate that the development strategy for the Tangkolak mangrove ecotourism area falls within the coordinates (2.5; 2.6) in quadrant I, signifying a combination of strengths and opportunities (SO strategy).